2018
DOI: 10.1088/2057-1976/aab974
|View full text |Cite
|
Sign up to set email alerts
|

Bone fracture monitoring using implanted antennas in the radius, tibia and phalange heterogeneous bone phantoms

Abstract: Bone fracture monitoring using implanted antennas in the radius tibia and phalange heterogeneous bone phantoms. Biomedical Physics & Engineering Express, 4, 045006.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…We have used this system to report the temporal in vivo load‐sharing of a fixation plate in a large animal model and conclusively shown that these data can be used to predict the fracture's healing cascade . For fractures treated with external fixation, it has been proposed to utilize the implanted pins themselves as antennas to monitor fracture healing . Whereas this approach detects changes in the electromagnetic properties of the tissue in the fracture space throughout healing, our group's approach uses external antennas to detect changes in the mechanical stability of the fracture.…”
mentioning
confidence: 99%
“…We have used this system to report the temporal in vivo load‐sharing of a fixation plate in a large animal model and conclusively shown that these data can be used to predict the fracture's healing cascade . For fractures treated with external fixation, it has been proposed to utilize the implanted pins themselves as antennas to monitor fracture healing . Whereas this approach detects changes in the electromagnetic properties of the tissue in the fracture space throughout healing, our group's approach uses external antennas to detect changes in the mechanical stability of the fracture.…”
mentioning
confidence: 99%
“…A dual monopole antenna was proposed in [ 20 ] for monitoring the fracture of the bone, which was simulated with a voxel model of a 26-year-old female on CST Microwave Studio virtual version as shown in Figure 15 . The restoration process of fractured bone was monitored by a monopole antenna placed on both sides of the fracture and determined the bone condition by transmitting power from one monopole to another monopole.…”
Section: Summary Of the Existing Implant Antenna Technologymentioning
confidence: 99%
“… Electric field distribution at 2.5 GHz: during 0% bone damage period ( a ), fractured bone period ( b ) [ 20 ]. …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations